2014
DOI: 10.1037/a0037509
|View full text |Cite
|
Sign up to set email alerts
|

Vagal activity is quadratically related to prosocial traits, prosocial emotions, and observer perceptions of prosociality.

Abstract: In the present article, we introduce the quadratic vagal activity-prosociality hypothesis, a theoretical framework for understanding the vagus nerve's involvement in prosociality. We argue that vagus nerve activity supports prosocial behavior by regulating physiological systems that enable emotional expression, empathy for others' mental and emotional states, the regulation of one's own distress, and the experience of positive emotions. However, we contend that extremely high levels of vagal activity can be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
107
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 103 publications
17
107
1
1
Order By: Relevance
“…Even in healthy subjects, higher resting vagal tone has been associated with positive mood, optimism, and personality traits that promote social engagement (31,44). Exaggerated resting vagal tone, however, may also be maladaptive and put individuals at risk for dysregulated positive emotion (i.e., mania) or reduced prosociality (63,64).…”
Section: Localization and Lateralization Of Cortical Cardiac Parasympmentioning
confidence: 99%
“…Even in healthy subjects, higher resting vagal tone has been associated with positive mood, optimism, and personality traits that promote social engagement (31,44). Exaggerated resting vagal tone, however, may also be maladaptive and put individuals at risk for dysregulated positive emotion (i.e., mania) or reduced prosociality (63,64).…”
Section: Localization and Lateralization Of Cortical Cardiac Parasympmentioning
confidence: 99%
“…This positive association between RSA and prosocial behavior is in keeping with theoretical postulations that vagal tone is particularly important for interpersonal behavior and that it allows for sustained attention in the context of safe social interactions (Porges and Furman, 2011; Porges, 2001). In a set of studies with adults, Kogan et al (2014) also found evidence for a U-shaped relation of vagal reactivity to prosocial behavior (see also Beauchaine et al, 2007; Marcovitch et al, 2011 for similar quadratic relations to RSA withdrawal). Kogan et al (2014) contend that some degree of sympathetic arousal (i.e., moderate parasympathetic tone) is necessary to effectively demonstrate empathy for others while maintaining a calm, attentive state.…”
Section: Discussionmentioning
confidence: 87%
“…Our approach is based on a standard definition of compassion as a 'sensitivity to suffering in self and others with a commitment to try to alleviate and prevent it' [21,46,64,104]. The impetus for this research was inspired by a wealth of research showing e that developing caring and compassion-focused motives for self and others has a range of benefits: on genetic expression [14,31,109], physiological processes [9,68,71,73,107,108], psychological processes [63,64,66,108], and social relationships [16,18,100]. Cultivating compassion for self and others has also become a central focus for the development of psychotherapies [35,37,40,61,67,69,77,96].…”
Section: Introductionmentioning
confidence: 99%